2006
DOI: 10.1073/pnas.0605422103
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular protein interaction mapping with FRET hybrids

Abstract: A quantitative methodology was developed to identify protein interactions in a broad range of cell types by using FRET between fluorescent proteins. Genetic fusions of a target receptor to a FRET acceptor and a large library of candidate peptide ligands to a FRET donor enabled high-throughput optical screening for optimal interaction partners in the cytoplasm of Escherichia coli. Flow cytometric screening identified a panel of peptide ligands capable of recognizing the target receptors in the intracellular env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
85
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 52 publications
(55 reference statements)
1
85
0
Order By: Relevance
“…We have previously shown that this technique can be used to detect molecular interactions in situ in Drosophila brain tissue (26). FRET has been previously shown to identify proteins that are in extremely close proximity (Ͻ5 nm) and is highly correlated with a direct molecular interaction (27). Drosophila brain tissues were incubated with antibodies directed against Polo kinase and RacGAP or Pav-KLP and stained with secondary antibodies labeled with the Cy3 and Cy5 fluorophores, respectively.…”
Section: -L) Polo Kinase Interacts Directly With Racgap In the Cytokmentioning
confidence: 99%
“…We have previously shown that this technique can be used to detect molecular interactions in situ in Drosophila brain tissue (26). FRET has been previously shown to identify proteins that are in extremely close proximity (Ͻ5 nm) and is highly correlated with a direct molecular interaction (27). Drosophila brain tissues were incubated with antibodies directed against Polo kinase and RacGAP or Pav-KLP and stained with secondary antibodies labeled with the Cy3 and Cy5 fluorophores, respectively.…”
Section: -L) Polo Kinase Interacts Directly With Racgap In the Cytokmentioning
confidence: 99%
“…To address this shortcoming, several groups have exploited oligomerizationassisted reassembly of split enzymes such as adenylate cyclase (20), ␤-lactamase (Bla) (21), and dihydrofolate reductase (22,23), as well as split fluorescent proteins (24,25). Alternatively, a number of methodologies for detecting interacting proteins in bacteria have been developed that do not rely on interaction-induced complementation of protein fragments, but instead use phage display (26), FRET (27), and cytolocalization of GFP (28).…”
mentioning
confidence: 99%
“…These reporters consist of an optimized FRET pair of fluorescent proteins, YPet and CyPet, which were recently described by Daugherty and coworkers [24] for the study of molecular interactions in vivo [39]. The CyPet and YPet proteins were linked together by a flexible linker containing a consensus recognition site for LF protease [36] flanked at both its N-and C-termini by several repeats of the flexible tripeptide Gly-Gly-Ser [41].…”
Section: Discussionmentioning
confidence: 99%